This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Complete the square: ∫ 0 1 ( x − 2 3 ) 2 − 4 1 ( 3 x 3 − x 2 + 2 x − 4 ) d x = ∫ 0 1 2 ( 2 x − 3 ) 2 − 1 ( 3 x 3 − x 2 + 2 x − 4 ) d x Now by substitution u = 2 x − 3 such that
d x = 2 1 d u x 2 = 4 ( u + 3 ) 2 x 3 = 8 ( u + 3 ) 3 = 1 6 1 ∫ 0 1 u 2 − 1 ( 3 u 3 + 2 5 u 2 + 7 7 u + 5 5 ) d u
Now we have a simple trigonometric substitution u = sec ( v )
d u = sec ( v ) tan ( v ) d v ∫ 0 1 sec 2 ( v ) − 1 sec ( v ) [ 3 u sec 3 ( v ) + 2 5 sec 2 ( v ) + 7 7 sec ( v ) + 5 5 ] tan ( v ) d v = ∫ 0 1 sec ( v ) [ 3 u sec 3 ( v ) + 2 5 sec 2 ( v ) + 7 7 sec ( v ) + 5 5 ] d v = 3 ∫ 0 1 sec 4 ( v ) d v + 2 5 ∫ 0 1 sec 3 ( v ) d v + 7 7 ∫ 0 1 sec 2 ( v ) d v + 5 5 ∫ 0 1 sec ( v ) d v The first integral:
∫ sec 4 ( v ) d v = ∫ sec 2 ( v ) [ tan 2 ( v ) − 1 ] d v Let w = tan ( v ) , d w = sec 2 ( v ) d v
∫ ( w 2 − 1 ) d w = 3 w 3 − w = 3 tan 3 ( v ) − tan ( v )
Then by the reduction formula we have that:
∫ sin n ( v ) d v = n − 1 n − 2 ∫ sec n − 2 ( v ) d v + n − 1 sec n − 2 ( v ) tan ( v ) Therefore, for n = 3
∫ sec 3 ( v ) d v = 2 sec ( v ) tan ( v ) + 2 1 ∫ sec ( v ) d v
We have a standard integral for n=2
∫ sec 2 ( v ) d v = tan ( v ) For n = 1 , we expand and substitute: ∫ sec ( v ) d v = ∫ tan ( v ) + sec ( v ) sec ( v ) [ tan ( v ) + sec ( v ) ] d v Let
u = tan ( v ) + sec ( v ) d v = sec 2 ( v ) + sec ( v ) tan ( v ) 1 d u ∫ sec ( v ) d v = ∫ u 1 d u = ln u = ln ( tan ( v ) + sec ( v ) )
Then finally we have:
3 ∫ 0 1 sec 4 ( v ) d v + 2 5 ∫ 0 1 sec 3 ( v ) d v + 7 7 ∫ 0 1 sec 2 ( v ) d v + 5 5 ∫ 0 1 sec ( v ) d v = 2 1 3 5 ln ( tan ( v ) + sec ( v ) ) + tan 3 ( v ) + 2 2 5 tan ( v ) sec ( v ) + 8 0 tan ( v )
Now undo the substitutions one step at a time, simplify and we arrive at [ 1 6 1 3 5 ln ( ∣ 2 x 2 − 3 x + 2 + 2 x − 3 ∣ ) + x 2 − 3 x + 2 ( 1 6 x 2 + 5 2 x + 2 0 2 ) ] 0 1 = − 2 . 9 8 1 2 6 6 9 4 4
Therefore the PIN is 2981